Schaum's outline of theory and problems of general, organic and biological chemistry - Odian, George (McGraw-Hill, 1994)
The book covers course fundamentals and supplements any class text; teaches effective problem-solving techniques. It includes 1.442 solved problems with complete solutions, also includes 544 supplementary problems answers.